Domestic Hygiene Practices and Factors that Risks for Childhood Diarrhoea Among Under Five Children in Isolated Chars of Gaibandha, Bangladesh - Hossain, Muhammad Belal; Akther, Lutfa; Awwal, AAM Anisul (Anwer Khan Modern Medical College Journal, 2019)
Background: Worldwide diarrheal disease is the second leading cause of death in under-five years children. In Bangladesh diarrhoea kills half million under-five children every year second to pneumonia. The study was aimed to assess the domestic hygiene practices and find the factors that risked for diarrheal disease in under-five children among the families that resides in isolated chars of Gaibandha district. Method: A community based cross-sectional study design was employed in 2011 at three unions of Gaibandha district. Random sampling technique was employed to select 322 households that had at least one under-five children. Data was collected using pretested structured questionnaire. Result: A total of 322 children were enrolled. The overall diarrhoea prevalence was 20.8%. About 71% (n=255) of households collected drinking water from improved water sources and only 10.8% (n=17) had been using river water for their cooking. We found a lower prevalence of diarrhoea in children whose mother had a higher education level. More than 60% mothers didn't wash their hands before feeding their children. A good scenario has been observed that babies were breastfed for sufficient time period. Apart from diarrhoea, Otitis media and skin diseases were significantly found in chars babies. About 20% of the babies were found not immunized and 43.2% found immunized and over 40% partially immunized. Half of the families were found deprived from primary health care facilities and there were found only one satellite clinic in the study sites. Conclusion: The level of diarrheal disease variation was varied due to maternal education, socio-economic status, personal hygiene, waste disposal system and public awareness. Thus enhancing community based behavioural change communication that emphasize on personal hygiene and sanitation should be strengthening to reduce childhood diarrhoea. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 5-10